Hybrid ZnO : polystyrene nanocomposite for all-polymer photonic crystals - Lova, Paola (2015)
We report on ZnO nanoparticles-polystyrene (PS) nanocomposites (NC) engineered to modify PS matrix permeability and refractive index (n), and to fabricate 1D all-polymer photonic crystals (PC) for sensing applications. The new NC can be easily processed from solutions to prepare high quality thin films by spin coating. ZnO nanoparticles (n = 1.98) have been synthetized by solvothermal route and grafted with a silane to reduce phase segregation in the PS matrix (n = 1.58). Such procedure led to an increase of the matrix refractive index of about 1%. By casting alternated layers of the NC and cellulose acetate (CA, n = 1.46), we fabricated free-standing and flexible distributed Bragg reflectors (DBRs) of excellent optical quality. Preliminary results on the use of such DBRs as solvent vapor sensors are reported.